Body dissatisfaction and disordered eating are prevalent problems among U.S. young people from diverse socioeconomic backgrounds: Findings from the EAT 2010–2018 study. (August 2021) - Larson, Nicole; Loth, Katie A.; Eisenberg, Marla E.; Hazzard, Vivienne M.; Neumark-Sztainer, Dianne
Abstract: Purpose: Body dissatisfaction and disordered eating are linked to adverse health consequences. Research describing socioeconomic patterns in the prevalence of these problems is important for informing the design of health services and efforts to improve health equity. Methods: Population-based cohort study (EAT 2010–2018: Eating and Activity over Time) of socioeconomically and ethnically/racially diverse U.S. young people who completed surveys as adolescents in 2009–2010 (mean age = 14.5 years) and as emerging adults in 2018 (mean age = 22.0 years). Participants were recruited from 20 schools in Minneapolis-St. Paul, Minnesota. Household socioeconomic status was determined using adolescent report of parental education, employment, and public assistance benefits. Analyses were conducted using data from 1531 participants and regression models that accounted for repeated measures within individuals. Results: Among females, high body dissatisfaction and unhealthy weight control behaviors (e.g., skipping meals) were more prevalent and regular use of lifestyle weight management behaviors (e.g., exercise) was less prevalent in the low SES group as compared to the middle and/or upper SES groups ( p ≤ .010). Among males, thinness-oriented dieting, unhealthy weight control behaviors, and extreme weight control behaviors (e.g., taking diet pills) were all more prevalent in the low SES group as compared to the middle and/or upper SES groups (p ≤ .010). Few differences were observed across SES groups in models that adjusted for ethnic/racial identity and body mass index. Conclusions: There is a need for greater attention to the reach and relevance of efforts to prevent disordered eating and improve body satisfaction to ensure efforts benefit young people across SES groups. Highlights: Body dissatisfaction and disordered eating are prevalent in all socioeconomic groups. Socioeconomic differences exist in females' weight behaviors (e.g., limiting soda). Males of lower socioeconomic status use more unhealthy weight control behaviors.